Peran Mediasi Inovasi: Hubungan Antara Harga dan Kualitas Pelayanan dengan Kepuasan Konsumen - Eka Pranajaya; Teddy Setiawan; Deri Firmansyah; Dwinanto P. Susetyo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Price, service quality and innovation change the management game in an effort to find the right alternative to increase customer satisfaction as a form of adaptability. This study aims to examine the mediating role of innovation on the relationship between price and service quality to predict consumer satisfaction. The sample used as many as 160 with quota sampling technique. Path analysis was selected using the help of the Eviews v10 program, the indirect effect was carried out with the Sobel test. The findings of structural analysis I, show that price and service quality have a significant positive effect on innovation both individually and simultaneously. The results of structural analysis II, show that service quality directly has a significant positive effect on consumer satisfaction, while price directly has a significant negative effect on customer satisfaction. From the Sobel test, it is known that there is a significant positive causal effect of price and service quality on consumer satisfaction with the mediating role of innovation. Other causal effects related to price, service quality, the role of innovation and customer satisfaction still need to be investigated and developed.